PENGARUH STRUKTUR MODAL, KEPEMILIKAN MANAJERIAL, PERTUMBUHAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Amara, Miranda Seni; Kusmayadi, Dedi (JURNAL AKUNTANSI, 2025)
This study investigates the effects of capital structure, managerial ownership, firm growth, and profitability on firm value among companies included in the LQ45 index of the Indonesia Stock Exchange over the 2018–2023 period. Adopting a verificative quantitative approach, the study utilizes secondary data obtained from corporate annual reports and applies fixed-effects panel data regression for empirical analysis. The sample is selected using purposive sampling. The results demonstrate that capital structure, managerial ownership, firm growth, and profitability jointly exert a significant influence on firm value. Partially, capital structure has a significantly negative effect, managerial ownership has a negative but statistically insignificant effect, while firm growth and profitability show positive yet insignificant effects on firm value. These findings indicate that firm value in large-cap and highly liquid stocks is driven primarily by the combined performance of corporate financial attributes rather than by isolated financial indicators. This study provides empirical contributions to the literature on firm value determinants in emerging capital markets